2021
DOI: 10.1182/blood-2021-147433
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Treatment Patterns in Patients with Aggressive B-Cell Lymphoma after Failure of Anti-CD19 CAR T-Cell Therapy

Abstract: Background: Anti-CD19 chimeric antigen receptor T-cell therapy (CART) is a highly active therapy for relapsed/refractory (R/R) aggressive B-cell lymphoma. Nonetheless, most patients (pts) ultimately develop progressive disease (PD). There is little guidance on the optimal treatment approach(es) for these pts. We performed a multicenter retrospective analysis with a primary objective to assess treatment patterns and outcomes in pts with R/R aggressive B-cell lymphoma who develop PD after anti-CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…Similarly, Zurko et al demonstrated in their population the highest response rates after R-Pola-Benda regimen (73% overall response rate and 40% CR, respectively). 26 Other studies suggest a role for antiprogrammed cell death protein 1 drugs 27,28 in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Zurko et al demonstrated in their population the highest response rates after R-Pola-Benda regimen (73% overall response rate and 40% CR, respectively). 26 Other studies suggest a role for antiprogrammed cell death protein 1 drugs 27,28 in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…The median PFS was 1.2 mo for BTKi (n=8). BTKi may be attributed a immunomodulatory effect on previously CARTs [67]. The exact mechanism of the synergistic effects of BTKi and CAR T-cells is unclear.…”
Section: Combination Therapy With Targeted Agentsmentioning
confidence: 99%
“…is an ADC consisting of an anti-CD79b mAb and an antimitotic agent called mono-methyl auristatin E, which has been approved for patients with R/R LBCL. Studies of CD19 CAR T-cell treatment failure have shown that, among all patients receiving further treatment, PV-based therapy was associated with the highest ORR (52-73%) and CR(35-40%) in patients with PD [67,77]. Chemotherapy was associated with the poorest survival (6-month OS 25%; 95% CI, 11-59), whereas PV-based treatment was associated with a survival of 67% (50-89%) [77].…”
Section: Polatuzumab Vedotin Polatuzumab Vedotin (Pv)mentioning
confidence: 99%
See 2 more Smart Citations